Diversity and Ecophysiology of the Genus OLB8 and Other Abundant Uncultured Saprospiraceae Genera in Global Wastewater Treatment Systems - Kondrotaite, Zivile; Valk, Laura C.; Petriglieri, Francesca; Singleton, Caitlin; Nierychlo, Marta; Dueholm, Morten K. D.; Nielsen, Per H. (Frontiers in Microbiology, 2022)
The Saprospiraceae family within the phylum Bacteroidota is commonly present and highly abundant in wastewater treatment plants (WWTPs) worldwide, but little is known about its role. In this study, we used MiDAS 4 global survey with samples from 30 countries to analyze the abundance and distribution of members of Saprospiraceae. Phylogenomics were used to delineate five new genera from a set of 31 high-quality metagenome-assembled genomes from Danish WWTPs. Newly designed probes for fluorescence in situ hybridization (FISH) revealed rod-shaped morphologies for all genera analyzed, including OLB8, present mostly inside the activated sludge flocs. The genomes revealed potential metabolic capabilities for the degradation of polysaccharides, proteins, and other complex molecules; partial denitrification; and storage of intracellular polymers (glycogen, polyphosphate, and polyhydroxyalkanoates). FISH in combination with Raman microspectroscopy confirmed the presence of intracellular glycogen in Candidatus Brachybacter, Candidatus Parvibacillus calidus (both from the former genus OLB8), and Candidatus Opimibacter, and the presence of polyhydroxyalkanoates in Candidatus Defluviibacterium haderslevense and Candidatus Vicinibacter. These results provide the first overview of the most abundant novel Saprospiraceae genera present in WWTPs across the world and their potential involvement in nutrient removal and the degradation of macromolecules.